The relationship between hypertriglyceridemic wait-to-height ratio and hypertension-diabetes comorbidity among older adult - Ping Zhang; Yangyang Xiong; Menghan Chen; Huaide Zhang; Nan Sun; Fan Wu; Jiayu Yang; Yongcheng Ren; Yongcheng Ren (Frontiers Media S.A., 2023)
ObjectiveLimited information is available on the effect of hypertriglyceridemic waist-to-height ratio (HTHWH) and hypertension-diabetes comorbidity (HAD) in older adult people. We aimed to explore the relationship between HTHWH and HAD for the co-management of hypertension and diabetes mellitus in the older adult.MethodsA cross-sectional study, randomized cluster sampling from 10 community health service centers, and multivariate logistic regression were used in this study. A total of 3,501 participants aged 65 years or older recruited between January 2019 and December 2019 completed the study.ResultsAmong 3,501 participants, the median age was 69.96 years, and 42.50% were men. A total of 1,207 subjects were in the HTHWH group, and the prevalence rate of HAD was 17.23% in this group. Multivariate logistic regression analysis showed that, as compared with the normal group, the risk of HAD in the HTHWH group increased by 2.05 times (OR = 3.05, 95% CI: 2.06-4.51). The risks of hypertension or diabetes mellitus (HOD), hypertension, and diabetes mellitus were also increased in the HTHWH group, with their ORs (95%CIs) being 1.82 (1.44-2.29), 1.73 (1.38-2.17), and 2.28 (1.66-3.13), respectively.ConclusionHTHWH significantly increases the risk of HAD and can be used as a reliable tool to screen the high-risk population for HAD.